2012
DOI: 10.1002/ibd.22942
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal genome-wide methylation changes in inflammatory bowel disease

Abstract: Consistent differences in DNA methylation between IBD cases and controls at regulatory sites within these genes suggest that their altered transcription contributes to IBD pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
126
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(136 citation statements)
references
References 29 publications
5
126
3
2
Order By: Relevance
“…Studies have shown that DNA methylation is well correlated with various aspects of IBD, including disease duration and severity of inflammation (15,16). It is also known that the expression of histone deacetylase 3 (HDAC3), an epigenome-modifying enzyme, influences Significance TNFα is the key cytokine implicated in inflammatory bowel disease.…”
mentioning
confidence: 99%
“…Studies have shown that DNA methylation is well correlated with various aspects of IBD, including disease duration and severity of inflammation (15,16). It is also known that the expression of histone deacetylase 3 (HDAC3), an epigenome-modifying enzyme, influences Significance TNFα is the key cytokine implicated in inflammatory bowel disease.…”
mentioning
confidence: 99%
“…Moreover, low concordance rates have been observed in monozygotic twin studies (3), leading to the hypothesis that epigenetic regulation also contributes to IBD pathogenesis. Changes in DNA and histone modifications associated with epigenetic regulation have been detected in IBD patients (3,4,9,11,12), but direct links to the IBD intestinal pathology have not been established. However, recent work has shown that IEC-specific deletion of the histone deacetylase HDAC3 results in increased susceptibility to intestinal damage and inflammation, although specific molecular targets remain to be identified (13).…”
mentioning
confidence: 99%
“…Since epigenetic changes can also be detected in precancerous lesions tissues (Gonzalo et al, 2010) suggesting its potential role in the initial carcinogenesis (Petronis and Petroniene, 2000;Jawad, et al, 2011;Cooke, et al, 2012;Jenke and Zilbauer, 2012;Olaru, et al, 2012). Gene promoter hypermethylation in normal appearing colorectal mucosa has been suggested in the MGMT gene as well as, MLH1, TIMP3 and DAPK (Gonzalo, et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of gene silencing mediated by hypermethylation in IBD remains controversial, however considering the variable gene methylation prevalence reported in IBD-CRCs (Fleisher, et al, 2000;Konishi, et al, 2007;Dhir, et al, 2008;Cooke, et al, 2012;Olaru, et al, 2012).…”
Section: Discussionmentioning
confidence: 99%